2013
DOI: 10.1186/1743-422x-10-18
|View full text |Cite
|
Sign up to set email alerts
|

A possible coincidence of cytomegalovirus retinitis and intraocular lymphoma in a patient with systemic non-Hodgkin’s lymphoma

Abstract: PurposeTo present a possible coincidence of cytomegalovirus retinitis and intraocular lymphoma in a patient with systemic non-Hodgkin’s lymphoma.Case presentationA 47-year-old woman presented with decreased visual acuity associated with white retinal lesions in both eyes. A history of pneumonia of unknown aetiology closely preceded the deterioration of vision. Five years previously the patient was diagnosed with follicular non-Hodgkin’s lymphoma. She was treated with a chemotherapy regimen comprised of cycloph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…Svozílková et al 2 reported a case of bilateral CMV retinitis in an HIV-negative patient with NHL, with a normal lymphocyte count, who had white retinal lesions in both eyes. Vitreous fluid analysis showed atypical lymphoid elements, highly suspicious of malignancy, but PCR testing confirmed the presence of CMV in the vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…Svozílková et al 2 reported a case of bilateral CMV retinitis in an HIV-negative patient with NHL, with a normal lymphocyte count, who had white retinal lesions in both eyes. Vitreous fluid analysis showed atypical lymphoid elements, highly suspicious of malignancy, but PCR testing confirmed the presence of CMV in the vitreous.…”
Section: Discussionmentioning
confidence: 99%
“…La littérature reporte aussi un cas de rétinite à CMV chez une patiente atteinte d'un lymphone non hodgkinien, chez laquelle un traitement combiné (oral et intraveineux) a été suffisant pour arrêter l'atteinte oculaire [8].…”
Section: Discussionunclassified
“…We identified 15 manuscripts with 24 cases of CMV retinitis in patients with lymphoma (Table ) . We excluded an additional three reports due to insufficient data …”
Section: Review Of the Literaturementioning
confidence: 99%
“…In nine of the 18 cases in which outcomes were described, the retinitis completely resolved. In four cases, CMV retinitis recurred after initial therapy . One episode was in the setting of initiating chemotherapy (unknown if the patient was still on antiviral therapy), two were after stopping anti‐CMV therapy, and one was during maintenance therapy with oral valganciclovir.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation